Evaluation Of Some Scab Resistant Apple Hybrids As Early Season Genotypes (Applied Biological Research, 2014)
Five scab-resistant hybrids [ASPE-99 (Sunhari x Prima), ASPE-36 (Lal  Ambri x Prima), ALPE-99 (Sunhari x Prima), ASPE-22 (Sunhari x  Prima) and ALPE-57 (Lal Ambri x Prima)] developed by SKUAST Kashmir, were evaluated for phenological, pomological and storage  characteristics in 2009 and 2010. The days taken to full bloom ranged  between 80.5 to 86.5 in hybrids and 76.5 to 83.0 in check cultivars.  ASPE-36 and ASPE-99 matured earlier (82 days for fruit development)  while ALPE-57, ASPE-22 and ALPE-99 matured 6.0-16.5 days later.  Fruit shape in hybrids was oblate and slight to moderately lopsided with  smooth surface. Fruits were crisp, juicy, moderately flavoured and red  coloured with yellowish background and creamy flesh. Fruit firmness  was maximum in ALPE-57 followed by ALPE-99 and ASPE-36. Hybrids  significantly varied in fruit size and weight with high values in ALPE 99, ALPE-57 and ASPE-22. Hybrids had higher TSS and total sugars  and were less acidic than checks. Total sugar was maximum and titrable  acidity minimum in ASPE-22. The storage life of hybrids was higher  than control with maximum storage life of 156-172 days under CA  storage, 73-88 days under refrigeration and 34-45 days under normal  storage conditions. Hybrids ASPE-99, ASPE-22 and ALPE-57 were  identified as prospective genotypes for release as improved early season  scab-resistant cultivars.
Keywords: Apple hybrids; flower phenology; fruit characteristics; scab resistant